Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1039/c0lc00613k
|View full text |Cite
|
Sign up to set email alerts
|

A first step towards practical single cell proteomics: a microfluidic antibody capture chip with TIRF detection

Abstract: We have developed a generic platform to undertake the analysis of protein copy number from single cells. The approach described here is 'all-optical' whereby single cells are manipulated into separate analysis chambers using an optical trap; single cells are lysed by a shock wave caused by laser-induced microcavitation; and the protein released from a single cell is measured by total internal reflection microscopy as it is bound to micro-printed antibody spots within the device. 10The platform was tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 18 publications
2
79
0
Order By: Relevance
“…We have previously developed single cell protein analysis methods and have tested and validated them on a range of cell lines [14][15][16]. These methods are based on microfluidics, with optical trap cell handling and incorporating single molecule detection.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed single cell protein analysis methods and have tested and validated them on a range of cell lines [14][15][16]. These methods are based on microfluidics, with optical trap cell handling and incorporating single molecule detection.…”
Section: Introductionmentioning
confidence: 99%
“…This would provide a truly quantitative read-out of cellular behavior. 10 Optical traps are also useful for injecting material. We found that cells grown on amorphous silicon (as used in solar panels) selectively and reversibly developed membrane nanopores under illumination from IR lasers, to which they would typically be transparent.…”
Section: 1117/21201605006474 Page 2/3mentioning
confidence: 99%
“…Sonoporation, or sonically enhanced permeability of cell membranes, has been demonstrated using both laser and acoustically induced microcavitation [9]. Single cell lysis via shock waves caused by laser induced microcavitation, has facilitated single cell proteomics [10].…”
Section: Introductionmentioning
confidence: 99%